Hetero-hierarchical tessellated architected materials towards high mechanical performances and high manufacturability - Jiacheng Wu; Fan Yang; Cuiping Bai; Junying Min; Zhenhua Song; Hualin Fan (Virtual and Physical Prototyping)
High-fidelity additive manufacturing of metallic lattice material remains challenging because of the likelihood of introducing manufacturing defects during the printing process, which weakens the mechanical performance and tunability. To address this challenge, we propose a hetero-hierarchical tessellation strategy integrating lattice cells with Miura-ori configuration to achieve a high manufacturing fidelity and strong mechanical performance. The high manufacturing fidelity was demonstrated through the micro-CT analysis on the specimens prepared by laser powder bed fusion technology, and the experimental compressive behaviors aligned well with the numerical simulations. The lattice tessellation mitigates the stress concentration in the origami materials during the crushing process, enhancing the specific stiffness, specific strength, and specific energy absorption (SEA) by over 35% compared to the case without lattice tessellation. By leveraging the hierarchical characteristics, the mechanical property space can be further broadened and improved by combining different lattice and origami types. This hetero-hierarchical tessellation strategy establishes a generalizable paradigm for designing architected materials with high designability, manufacturability, multifunctionality and superior mechanical performance.